MODEL FOR HANDLING REQUESTS AT THE STAGE OF PROVIDING SERVICES TO USERS - KONONOVA, IRYNA; KREDENTSER, BORYS; KRYLOV, OLEKSII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
A comprehensive approach to modeling request handling processes at the stage of providing services to users in intelligent service centers (ISC) is presented. The influence of the architectural and functional features of ISCs on the probabilistic and temporal characteristics of the service process is taken into account, in particular the topology of the request path, the organization of the distribution system (DS), the number and structure of service devices (SD), the discipline of queue formation, and the specifics of the implementation of the requested services.A classification of ISC structures is proposed in four variants: an integrated model with a switching station; a model with a dedicated DS without queues; a model with queues for each service; a two-level model with a common queue and subsequent routing by service. Each option is formalized by a corresponding mathematical model of queuing systems. For their analytical description, the classical Erlang formulas and the N. Buchman method were used, which made it possible to determine the probabilities of SD occupancy, the occurrence of queues, the level of losses, and the degree of resource utilization.A numerical analysis of the model parameters was performed, and nomograms were constructed that demonstrate the dependence of service efficiency on the number of devices, system load, and the accepted queue organization model. It was shown that dividing service devices into highly specialized groups with low traffic volumes leads to an overuse of resources. A two-level ISCs model has been determined to be optimal for medium traffic conditions, providing a balance between service quality and hardware cost-effectiveness.The results of the study can be applied in the design and optimization of ISCs structures in modern electronic communication networks, including IP telephony systems and service platforms for cloud communications.
Keywords: intelligent service center; IP telephony; request service model; quality of service; electronic communications network